2008
DOI: 10.1016/j.jspr.2008.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size of soft wheat flour on the development of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae)

Abstract: a b s t r a c tThe effect of soft wheat flours, characterized by different particle size, protein and starch content, on the development of Ephestia kuehniella was studied. The attractiveness of the substrata to first and third instar larvae was also considered.The different protein content of the flours did not significantly affect the development of E. kuehniella, nor did it affect the ability of the flours to attract larvae. In tests with soft wheat flours with the same nutritional value but different parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…Ephestia kuehniella were reared successfully for multiple generations on a standard, reduced, or minimal larval diet; however, the immatures developed fastest on the standard diet, the female pupae had the greatest mass, and more adults emerged. Previously, larvae reared on durum wheat flour compared to soft wheat flour also had a shorter development time and the adults produced more progeny (Locatelli et al 2008). This was attributed to a higher protein content and quantity of water-soluble and lipo-soluble vitamins in the durum wheat flour-based diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ephestia kuehniella were reared successfully for multiple generations on a standard, reduced, or minimal larval diet; however, the immatures developed fastest on the standard diet, the female pupae had the greatest mass, and more adults emerged. Previously, larvae reared on durum wheat flour compared to soft wheat flour also had a shorter development time and the adults produced more progeny (Locatelli et al 2008). This was attributed to a higher protein content and quantity of water-soluble and lipo-soluble vitamins in the durum wheat flour-based diet.…”
Section: Discussionmentioning
confidence: 99%
“…tends to be expensive and labor-intensive (Wang et al 2014). However, the Mediterranean flour moth can be reared on simple and inexpensive diets, such as wheat flour and many other foods (Stein and Parra 1987, Rodriguez-Menendez et al 1988, Magrini et al 1995, Filho et al 2001, Ci et al 2005, Locatelli et al 2008). In an attempt to reduce the cost of host production, larvae of the rice moth have been reared on relatively inexpensive cereals, such as finger millet, Eleusine coracana L. Gaertn; soft white wheat, Triticum aestivum L.; short-grained white rice, Oryza sativa L.; and durra sorghum, Sorghum bicolor L. (Nathan et al 2006).…”
mentioning
confidence: 99%
“…The recently hatched eggs were shipped to Montpellier's laboratory (France) in sealed containers under controlled conditions (15°C at 75% relative humidity). The E. kuehniella larvae were reared on hard wheat semolina (Locatelli, Limonta, & Stampini, 2008). Throughout the experiments, the insect cultures were maintained at a constant temperature (25 ± 1°C), a 14L:10D photoperiod and a 65 ± 5% relative humidity (Jacob & Cox, 1977).…”
Section: E Kuehniella Larvaementioning
confidence: 99%
“…Almost half (49.7%) of the particle size in semolina is between 212 μm and 354 μm; dust, collected at 7.5 and 15 m height, consists of particle sizes less than 106 μm (79.10% and 62.69%, respectively). Locatelli et al (2008) observed that the particle size of soft wheat flours influences both the adult emergence percentage and the mean development time of E. kuehniella.…”
Section: Discussionmentioning
confidence: 96%